Prevalence and contributing factors of low birth weight babies in institutional delivery - Malla, Milan; Joshi, Dilip Raj; Chhetri, Kailash; Pandey, Prabin (Journal of Patan Academy of Health Sciences, 2015)
Introduction: Low Birth Weight (LBW) is a sensitive indicator of socio- economic conditions and indirectly measures the health of mother and child. Though, the health situation of Nepal has improved substantially over the years, LBW rate is still high. The present study explores the prevalence and contributing factors of LBW babies delivered in Patan Hospital.Methods: The data were collected retrospectively from patients’ record for babies born at Patan Hospital, Patan Academy of Health Sciences, Kathmandu, Nepal. Records were retrieved through systematic randomization and IBM SPSS 15.0 was used for analysis. Non-parametric tests were applied with correlation done between dependent and independent variables.Results: A total of 4395 birth occurred during the study period of which 527 met the study criteria and remaining were of normal birth weight. The prevalence of LBW was 11.99% and the average LBW was calculated as 2074.97 ± 344.425 grams. The factors associated with LBW included preterm babies (Pearson correlation coefficient = 0.554, p = 0.001 < 0.05) and oligohydramnious (Spearman’s correlation coefficient = 0.307, p= 0.019 < 0.05).Conclusions: This study suggests preterm babies and oligohydramnious to be contributing factors of LBW babies.Journal of Patan Academy of Health Sciences, Vol. 2, No. 1, 2015. page: 26-29